Patients with Prior Colectomy Who Undergo Primary Total Knee Arthroplasty may have Higher Risks of Reoperation - Mai, David H.; Zhang, Bruce B.; Uddin, Abdullah A.; Zhou, Jack J.; Paulino, Carl B.; Naziri, Qais (The Journal of Knee Surgery, 2025)
There is a lack of consensus on the effects of prior colectomy on health outcomes, particularly those that involve orthopedic procedures. We sought to characterize the association between prior colectomy and outcomes following primary total knee arthroplasty (TKA). We hypothesized that compared with patients without, those with prior colectomy who undergo primary TKA have higher odds of same-admission postoperative complication and reoperation. We performed a retrospective cohort study using the Healthcare Cost and Utilization Project (HCUP) National (Nationwide) Inpatient Sample (NIS) database to identify patients who underwent primary TKA. Patients with prior colectomy were propensity-score matched to patients without prior colectomy at a ratio of 1:50 by age, gender, race/ethnicity, Charlson–Deyo Comorbidity index, history of osteoporosis, history of smoking, insurance status, hospital size, hospital location and teaching status, and hospital ownership. Adjusted logistic regression analyses were used to determine the relationship between colectomy and the same-admission outcomes, postoperative complication, and reoperation. Overall, 894,911 patients underwent primary TKA during the study period. After propensity score matching (PSM), 2,625 (1.96%) patients were assigned to the cohort with prior colectomy, while 131,250 (98.04%) patients were assigned to the cohort without prior colectomy. Compared with patients without prior colectomy, those with prior colectomy who underwent primary TKA had no significantly higher odds of same-admission postoperative complication; however, they had 2.12 times higher odds (95% confidence interval: 1.04–4.31; p = 0.038) of same-admission reoperation. Compared with patients with no prior colectomy, those with prior colectomy who underwent primary TKA had no higher odds of postoperative complication but had over twice the odds of reoperation during the same admission for surgery. Further studies examining the role of the colon and microbiota may help to better understand outcomes associated with the history of prior colectomy in the setting of primary TKA. This study is a level III retrospective cohort study.
Keywords: colectomy; total knee arthroplasty; outcomes; epidemiology; complication; reoperation